Progressive Demyelination in the Presence of Serum Myelin Oligodendrocyte Glycoprotein-IgG: A Case Report - Gil-Perotin, Sara; Castillo-Villalba, Jéssica; Carreres-Polo, Joan; Navarré-Gimeno, Arantxa; Mallada-Frechín, Javier; Pérez-Miralles, Francisco; Gascón, Francisco; Alcalá-Vicente, Carmen; Cubas-Nuñez, Laura; Casanova-Estruch, Bonaventura (Frontiers in Neurology, 2018)
The clinical diagnosis of patients with autoantibodies directed to conformational myelin oligodendrocyte glycoprotein, (MOG)-IgG, can be challenging because of atypical clinical presentation. MOG-IgG seropositivity has been reported in several demyelinating diseases, including relapsing opticospinal syndromes (in the neuromyelitis optica spectrum disorders [NMOSD] and less frequently, in multiple sclerosis [MS]), but it has rarely been associated with the progressive course of disease. To contribute to the characterization of MOG-related demyelination, we describe the case of a patient with progressive demyelinating opticospinal disease, IgG-oligoclonal bands (OCB), and serum MOG-IgG.